Experimental Investigation of Load Effects on Diesel Engine Performance Using Waste Tire Oil Blended with Dexlite Fuel - Afkar, Irsyadul (Journal of Engineering and Science, 2024)
Waste tires represent a form of inorganic waste that resists natural degradation. In Indonesia, estimates suggest around 11 million tons of used tires accumulate annually, with volumes expected to rise each year. This trend poses future environmental challenges. To address this issue, the study examines converting waste tires into fuel oil. The objective focuses on assessing how blending waste tire oil with dexlite influences diesel engine operation. The research involves two phases: testing fuel characteristics from tire oil and evaluating diesel engine performance. Laboratory tests yield tire oil properties including a heating value of 43,080 kJ/kg, viscosity of 1.12 mm²/s, density of 877 kg/m³, and cetane index of 97.1. Blends incorporate tire oil at 30%, 40%, and 50% with dexlite, tested on a diesel engine. Results indicate the highest engine power from the 30% blend (MB-30) at 1.132 HP under 2000 Watt load. The lowest specific fuel consumption occurs with the 50% blend (MB-50) at 0.528 kg/kWh under 1000 Watt load, while the highest thermal efficiency reaches 14.9% with MB-50 under 1000 Watt load.